Colorimetric Assessment of Surface Sealants for Discoloration of a Nanofilled Resin Composite - KORKUT, BORA (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: This in vitro study was aimed to assess the effect of different surface sealants on discoloration of a nonofilled resin-based composite quantitatively, using a colorimeter. Methods: 40 specimens were prepared using nanofilled resin composite, Filtek Universal Restorative (A2 shade, 3M, USA). Sprecimens were polymerized from both sides, polished using polishing discs (SofLex, 3M, USA) and divided by test groups (n = 10 for each), regarding the sealant used; Permaseal (Ultradent Products, USA), Biscover LV (Bisco, USA), Optiglaze Clear (GC Corp., Japan) and control group. Samples were discolored for 144 hours in coffee solution, and color measurements were performed using colorimeter (ShadeStar, Dentsply Sirona, USA). Nominal color codes of specimens regarding Vita Classical Shade Guide, were converted to corresponding numerical values. Level of color change after sealant application (Delta Vita1) and after discoloration (Delta Vita2) were calculated. Shapiro Wilk and Kruskal Wallis tests were used for statistical analyses. Results: Color changes in Permaseal, Optiglaze and control groups were significant (p < 0.001) compared to Biscover, for Delta Vita1 scores. Remarkable level of darkening was observed for all groups, for Delta Vita2 scores. Permaseal revealed significantly the highest level of darkening, among all (p < 0.001), but no difference with control group. Optiglaze showed significantly lower level of darkening compared to the control group (p < 0.001), whereas no difference with Biscover (p =>= 0.05). Biscover group showed similar level of darkening with Optiglaze and control groups (p >= 0.05). Conclusion: Permaseal sealant presented significantly the highest discoloration, whereas Biscover and Optiglaze sealants presented similar and lower. Colorimeter might be determined as repeatable method for measuring discoloration in vitro.
Keywords: Sealant; Biscover; Optiglaze; Permaseal; discoloration; nanocomposite; COLOR STABILITY; ROUGHNESS